Improving the fellowship interview experience for reproductive endocrinology and infertility candidates: a survey - Erika P. New, M.D., M.P.H; Papri Sarkar, M.D; Ruben J. Alvero, M.D; Anthony N. Imudia, M.D (Elsevier, 2020)
Objective: To collect data on the current reproductive endocrinology and infertility (REI) fellowship interview process so that it may be improved in the future. Design: Web-based cross-sectional survey. In addition, fellowship program directors and coordinators were contacted by e-mail. Setting: Survey data were collected after completion of the 2018 REI fellowship interview season. Patient(s): Not applicable. Intervention(s): None. Main Outcome Measure(s): Number of days used for interviews, missed opportunities to interview, frequency of travel to the same city, average money spent, recommendations for how the interview process could be improved. Result(s): There were 44 survey respondents. The mean number of interviews attended was 12.6 (range, 1-22). On average 13.4 (0-30) days off work were used to interview. About 68.1% (n = 30) missed an opportunity to interview at a program they were interested in. The most common reasons were the interview date was the same day as another interview, could not attend due to geographic location, and cost was too high. About 72% (n = 31) traveled to the same city more than once for an interview. The average cost per interview was $478 (range, $200-$1,000) and average cost per interview season was $5,660 (range, $900-$15,000). Fellowship program data were available from 43 of 48 programs contacted. The number of dates that had conflicting interviews scheduled were 26. Conclusion(s): These data highlight the need to coordinate the REI fellowship recruitment process between programs to reduce conflicting interview dates and mitigate costs to applicants. Based on these results, a concrete action plan is presented.